Timing-based mass measurement of exotic long-lived particles at the FCC-ee - R. Aleksan; E. Perez; G. Polesello; N. Valle (European Physical Journal C: Particles and Fields)
Abstract The very high luminosity run foreseen at the Z-pole for the FCC-ee will allow the detection in Z decays of new particles with very low couplings to the Standard Model. These particles can have measurable flight paths before they decay. If the timing and the position of the decay vertex can be measured with high precision, the mass of such particles can be measured by exploiting the constrained kinematics of an $$e^+e^-$$ e + e - collider. The mass resolution achievable with this technique is studied through a detailed analysis in the framework of a parametrised simulation of the performance of the IDEA detector. The adopted benchmark model is the production of Heavy Neutral Leptons, which is one of the key channels for new physics discovery at the FCC-ee.